2020
DOI: 10.1002/pon.5349
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of return to work after treatment for extremital soft tissue or bone sarcoma: Between distraction and leaving the disease behind

Abstract: Objective: We aimed to explore the return to work (RTW) experience of individuals in remission from extremital sarcoma.Methods: Using a qualitative survey design, we asked sarcoma survivors about their RTW experiences after treatment. Seven men and eight women (n = 15), 43 years old in average, participated. The majority had soft tissue sarcoma (n = 14) and no amputations (n = 14). We analysed data thematically through an inductive approach.Results: Participants' motivation to RTW and their experiences of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Approximately 60-70% of all cancer patients return to work [15,33], with the rest going into retirement or applying for disability pensions. Patients with sarcoma show the lowest return to work rates [34] and are considered to have a higher risk of not returning to work [35,36]. A study by Laros et al [37] showed that sarcoma patients in Germany had an average unemployment rate of 8.8 months and that for 67% of the sarcoma patients, the work situation changed after the unemployment phase.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60-70% of all cancer patients return to work [15,33], with the rest going into retirement or applying for disability pensions. Patients with sarcoma show the lowest return to work rates [34] and are considered to have a higher risk of not returning to work [35,36]. A study by Laros et al [37] showed that sarcoma patients in Germany had an average unemployment rate of 8.8 months and that for 67% of the sarcoma patients, the work situation changed after the unemployment phase.…”
Section: Discussionmentioning
confidence: 99%
“… 9 These effects can manifest as concentration problems, decreased energy and motivation, fatigue, changes in mood, chronic pain, and difficulties performing physical tasks, 26 in turn affecting the ability to attend school or work, and thus to achieve their educational and career goals. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Life after sarcoma treatment is complicated by the lasting physical and psychosocial impacts of the disease [13,14]. This is exacerbated by the somewhat naïve and commonly perceived expectation that patients and carers simply resume life as before treatment, despite this being rarely possible [15].…”
Section: Introductionmentioning
confidence: 99%